Intravenous dendritic cell administration enhances suppression of lung metastasis induced by carbon-ion irradiation. (27th February 2017) - Ando, Ken; Fujita, Hidetoshi; Hosoi, Akihiro; Ma, Liqiu; Wakatsuki, Masaru; Seino, Ken-ichiro; Kakimi, Kazuhiro; Imai, Takashi; Shimokawa, Takashi; Nakano, Takashi
Abstract: Carbon-ion radiotherapy (CIRT) is an advanced radiotherapy and has achieved good local control, even in tumors that are resistant to conventional photon beam radiotherapy (PBRT). However, distant metastasis control is an important issue. Recently, the combination of radiotherapy and immunotherapy has attracted the attention. In immunotherapy, dendritic cells (DCs) play a pivotal role in the anti-tumor immune system. However, the mechanisms underlying the combination therapy of DCs and radiotherapy have been unclear. In the present study, we evaluated anti-metastatic effects of this combination therapy, focused on the irradiation type and the route of DC administration, using a mouse model. C3H/He mice bearing NR-S1 cells were treated with CIRT or PBRT, using biologically equivalent doses. Subsequently, DCs were administered intratumorally (IT) or intravenously (IV). IV and IT DC administrations combined with CIRT to the local tumor, but not alone, significantly suppressed pulmonary metastasis, whereas the combination of DCs with PBRT suppressed metastasis at a relatively higher dose. Additionally, the anti-metastatic effect was greater in IV DC administration compared with in IT DC administration in both CIRT and PBRT. The expression levels of CD40 and IL-12 in DCs were significantly increased after co-culturing with CIRT-treated NR-S1 cells. In addition, IV administration of those co-cultured DCs significantly suppressed pulmonary metastasis. Furthermore, ecto-calreticulin levels from CIRT-treated NR-S1 cells significantly increased compared with those of a PBRT-treated tumor. Taken together, these results suggest that local CIRT combined with IV DCs augments an immunogenicity of the tumor cells by ecto-calreticulin expression and the maturation of DCs to stimulate anti-tumor immunity to decrease lung metastases.